Epidemiological profile of childhood leprosy cases in Maranhão between 2012 and 2021 (Research, Society and Development, 2023)
Leprosy affects Maranhão widely and the percentage of young age groups affected is considered an important indicator of the disease trend. The present study aims to verify the prevalence of cases of leprosy from 0 to 14 years old in the state of Maranhão, between the years 2012 to 2021. It is an epidemiological, descriptive, retrospective study, with a quantitative approach, carried out from the data of the SUS Ambulatory Information System (SIA/SUS) available by the Department of Informatics of the Unified Health System (DATASUS), in the period between 2012 and 2021, whose data included referred to the population aged between 0 and 14 years old, notified with leprosy in the state of Maranhão, excluding incomplete data and/or not filled in correctly. A total of 3469 leprosy diagnoses were reported, with the period between 2013 and 2015 having the highest number of notifications. In 2012, 440 cases were reported and in 2021, 168 cases, showing a reduction rate of 61.82% in the number of cases referring to the analyzed period. Of the clinical forms of leprosy, the most frequent was the borderline form, with a multibacillary appearance, with only one lesion found, compared to the other variations of the disease. Therefore, there was a significant reduction in the prevalence of cases between the investigated period. A delay in diagnosis is inferred, since the multibacillary form is the most prevalent clinical presentation. There is a need for further analyzes and investigations to improve both the treatment and prognosis of patients.